Integrated approach to revive unproductive brackish water aquaculture farm: A case study - Kassim, Zaleha (Yunus Centre For Social Business (YCSB@UKM), Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2016)
Good aquaculture practice is the key success factor as discipline in farm management and optimum production. Rearing activities depend on water supply as the basic need and it needs to be maintained to a limit so that the production will always at the optimum level. Dependency on the resources including the water and natural live feeds from the wild will always become the limitation. On the other hand, workers with very little knowledge and skill will affect the efficiency of the farm operation. These problems need to be identified and addressed by the top management as to improve the farm performance. A farm with the size of 20 hectares of marine tilapia was selected for the study. A series of field sampling was carried out for the first three months; to establish the environmental health status of the farm and to investigate the low survival of newly hatched larvae. Issues on management were surveyed through series of technical meeting with the middle and top management as well as the multitechnical agencies, which were held monthly. Basic water parameters showed that pH, salinity, dissolved oxygen and temperature were as the typical of brackish water condition. The temperature fluctuated and has higher range (between day and night) than the surrounding area of the mangrove forest. Biological analysis done on the water column and bottom sediment clearly indicated the low fertility condition of the farm. Technical group meetings gathered more information on the farm reported on the remain of sludge in the ponds which was stirred by certain fish handling activities, thus triggered the upwelling of pathogenic microbes into the water column and infect the growing fish. Results from technical meetings concluded that poor farm management and lack of standard operating procedure proved to be the main reason of the poor production from the farm. The farm is recommended to improve the system of water intake, water treatment and water circulation before each pond could be inoculated with microalgae and copepod population as an important step to rejuvenate the water condition in the farm. The biggest challenge in live feeds culture in the ponds is the warm temperature and high concentration of ion found in the water that microalgae and copepods need to adapt to. It is unclear if the farm has a proper Standard Operation Procedure for each cycle of the production which needs the top management to directly look into. The possible solution for the existing problem could be the integration of the water management system, operation practices, improving knowledge of the workers and commitment of the top management.